Regional Left Ventricular Myocardial Dysfunction After Cardiac Surgery Characterized by 3-Dimensional Strain. (May 2019) - Howard-Quijano, Kimberly; Methangkool, Emily; Scovotti, Jennifer C.; Mazor, Einat; Grogan, Tristan R.; Kratzert, Wolf B.; Mahajan, Aman
Abstract : BACKGROUND: Three-dimensional (3D) strain is an echocardiographic modality that can characterize left ventricular (LV) function with greater accuracy than ejection fraction. While decreases in global strain have been used to predict outcomes after cardiac surgery, changes in regional 3D longitudinal, circumferential, radial, and area strain have not been well described. The primary aim of this study was to define differential patterns in regional LV dysfunction after cardiac surgery using 3D speckle tracking strain imaging. Our secondary aim was to investigate whether changes in regional strain can predict postoperative outcomes, including length of intensive care unit stay and 1-year event-free survival. METHODS: In this prospective clinical study, demographic, operative, echocardiographic, and clinical outcome data were collected on 182 patients undergoing aortic valve replacement, mitral valve repair or replacement, coronary artery bypass graft, and combined cardiac surgery. Three-dimensional transthoracic echocardiograms were performed preoperatively and on the second to fourth postoperative day. Blinded analysis was performed for LV regional longitudinal, circumferential, radial, and area strain in the 17-segment model. RESULTS: Regional 3D longitudinal, circumferential, radial, and area strains were associated with differential patterns of myocardial dysfunction, depending on the surgical procedure performed and strain measure. Patients undergoing mitral valve repair or replacement had reduced function in the majority of myocardial segments, followed by coronary artery bypass graft, while patients undergoing aortic valve replacement had reduced function localized only to apical segments. After all types of cardiac surgery, segmental function in apical segments was reduced to a greater extent as compared to basal segments. Greater decrements in regional function were seen in circumferential and area strain, while smaller decrements were observed in longitudinal strain in all surgical patients. Both preoperative regional strain and change in regional strain preoperatively to postoperatively were correlated with reduced 1-year event-free survival, while postoperative strain was not predictive of outcomes. Only preoperative strain values were predictive of intensive care unit length of stay. CONCLUSIONS: Changes in regional myocardial function, measured by 3D strain, varied by surgical procedure and strain type. Differences in regional LV function, from presurgery to postsurgery, were associated with worsened 1-year event-free survival. These findings suggest that postoperative changes in myocardial function are heterogeneous in nature, depending on the surgical procedure, and that these changes may have long-term impacts on outcome. Therefore, 3D regional strain may be used to identify patients at risk for worsened postoperative outcomes, allowing early interventions to mitigate risk.